Edukasi Sekolah Ramah Lingkungan dan Kewirausahaan Melalui Pembuatan SILERY (Sabun Cuci Lerak Ecofriendly) di SMP Negeri 16 Malang - Mokhamad Husni Mubaroq; Laila Citra; Lidiyatul Muna; Nurul Ratnawati (Pusat Riset dan Inovasi Nasional, 2025)
The widespread use of chemical-based soaps has had a negative impact on the environment and human health. The hazardous chemicals contained in conventional cleaning products can pollute the air, damage ecosystems, and trigger skin and other health problems. This problem has become a concern in interest-based education, which emphasizes the importance of developing environmental awareness from an early age. In response to this issue, a community service activity was carried out at SMP Negeri 16 Malang by the Student Leadership Project Team of the Pre-Service PPG, State University of Malang. This activity aimed to raise ecological awareness and entrepreneurial spirit in students through a workshop on making natural soap from soap nuts, named